Modification of the Solid-State Nature of Sulfathiazole and Sulfathiazole Sodium by Spray Drying - Bianco, Stefano (Springer US, 2012)
Solid-state characterisation of a drug following pharmaceutical processing and upon storage is fundamental to successful dosage form development. The aim of the study was to investigate the effects of using different solvents, feed concentrations and spray drier configuration on the solid-state nature of the highly polymorphic model drug, sulfathiazole (ST) and its sodium salt (STNa). The drugs were spray-dried from ethanol, acetone and mixtures of these organic solvents with water. Additionally, STNa was spray-dried from pure water. The physicochemical properties including the physical stability of the spray-dried powders were compared to the unprocessed materials. Spray drying of ST from either acetonic or ethanolic solutions with the spray drier operating in a closed cycle mode yielded crystalline powders. In contrast, the powders obtained from ethanolic solutions with the spray drier operating in an open cycle mode were amorphous. Amorphous ST crystallised to pure form I at ≤35 % relative humidity (RH) or to polymorphic mixtures at higher RH values. The usual crystal habit of form I is needle-like, but spherical particles of this polymorph were generated by spray drying. STNa solutions resulted in an amorphous material upon processing, regardless of the solvent and the spray drier configuration employed. Moisture induced crystallisation of amorphous STNa to a sesquihydrate, whilst crystallisation upon heating gave rise to a new anhydrous polymorph. This study indicated that control of processing and storage parameters can be exploited to produce drugs with a specific/desired solid-state nature.